A Biographical Dictionary of People in Engineering : From Earliest Records to 2000 - Hall, Carl W. (Book collections on Project MUSE., 2008)
"This book lists the work and contributions of thousands of people from many countries, representing numerous fields of endeavor, over many centuries. This work contains the necrologies (names, dates, and a brief biography) up to the year 2000 of people involved in engineering and invention literature. This book is a must for reference collections and those in the media who cover the field of engineering advancement."--Publisher's website.